2021
DOI: 10.46483/deuhfed.829839
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Media on Children and Recommendations on the Use of Media

Abstract: Geçmişten günümüze teknolojinin ilerlemesi ve son dönemde COVID-19 pandemisi sebebiyle evde geçirilen sürenin uzaması, çocuk ve adölesanların dijital medya araçlarıyla geçirdiği süreyi hızla artırmıştır. Bu durum medya kullanım alışkanlıklarına bağlı olarak bazı olumlu ve olumsuz etkileri beraberinde getirmektedir. Medya araçlarının bilinçli, doğru ve amaca uygun kullanılması yaratıcılığı ve eleştirel düşünmeyi geliştirmekle birlikte yaşamı kolaylaştırmaktadır. Ancak bu araçların bilinçsiz ve kontrolsüz kullan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
3
0
2
Order By: Relevance
“…Gungor et al’s (2021) study found that students who communicate with individuals from different countries or cultures on social media have higher levels of intercultural effectiveness. Similarly, other study findings show that experiences abroad, having friends from different countries or cultures, or communicating on social media contribute positively to intercultural communication competence (Balcı & Öğüt, 2018; Türker, 2019; Uyanık & Tanrıverdi, 2021; Yılmaz et al, 2019). In line with these findings, this study determined that midwives who have friends from foreign/different cultures, follow their social media accounts, and have international experience demonstrate greater intercultural effectiveness.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Gungor et al’s (2021) study found that students who communicate with individuals from different countries or cultures on social media have higher levels of intercultural effectiveness. Similarly, other study findings show that experiences abroad, having friends from different countries or cultures, or communicating on social media contribute positively to intercultural communication competence (Balcı & Öğüt, 2018; Türker, 2019; Uyanık & Tanrıverdi, 2021; Yılmaz et al, 2019). In line with these findings, this study determined that midwives who have friends from foreign/different cultures, follow their social media accounts, and have international experience demonstrate greater intercultural effectiveness.…”
Section: Discussionsupporting
confidence: 51%
“…In this study, it was found that the scores of the participating midwives on the IES were partially at a good level. In different studies conducted in Türkiye, the participants’ levels of intercultural communication skills similarly ranged from moderate to high (Altınkaya & Amanak, 2020; Balcı & Öğüt, 2018; Gungor et al, 2021; Türker, 2019; Uyanık & Tanrıverdi, 2021; Yılmaz et al, 2019). The study results were evaluated as reflecting at least a moderate level of cultural communication skills among health care professionals in Türkiye’s multicultural structure, but the level is not yet optimal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alanyazın tarandığında dijital ortamlarda siber zorbalığa ilişkin birçok çalışmanın yapıldığı görülmüştür (Erdur Baker ve Kavşut, 2007;Yaman ve Peker, 2012;Akbaba ve Eroğlu, 2013;Eroğlu vd. 2015;Keser ve Kavuk, 2015;Yılmaz ve Güney, 2021). Bu araştırmanın amacı lisansüstü eğitim gören Türkçe öğretmenlerinin siber zorbalığa yönelik görüşlerini belirlemektir.…”
Section: Ijler International Journal Of Language and Education Researchunclassified